Research development with focus groups: experience with motorcycle couriers. A research strategy - Andréa Márian Veronese; Dora L Oliveira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This paper aims at discussing some aspects of the use of focus groups as a research strategy. The discussion has grounds in the qualitative research experience carried out in order to explore the motorcycle couriers point-of-view about traffic accident risks in their daily work. The paper describes the process of information gathered from the two focus groups since the field preparation until the information analysis generated in the interaction group. Point out the exploratory potentials of focus groups, as well as the importance of careful planning of fieldwork for the full use of this potential